Analysis of the impact hulling behaviour of paddy grains. (August 2022) - Chu, Yanhao; Han, Yanlong; Jia, Fuguo; Wang, Yinglong; Chen, Peiyu; Meng, Xiangyi; Zhang, Jincheng; Li, Anqi
Abstract : Rice hulling is the process of separating rice husks from the grain. Impact hulling is the norm for paddy grain processing because it produces higher quality hulled brown rice. However, high breakage fractions and low one-time hulling percentages can directly affect the quality of subsequent rice processing and restrict the development of paddy grain processing. Understanding the mechanism of paddy grain impact hulling is key to improving the performance of centrifugal rice hullers. In this paper, a single-seed impact test and the discrete element method (DEM) were used to simulate the paddy grain impact hulling. The effects of impact speed and angle on hulling percentage, breakage percentage and hulling pattern were investigated. The results showed that the effectiveness of paddy grain hulling after impact was due to the relative motion between rice husk and its kernel. The combined effect of impact and friction produces a relative motion between the husk and the kernel and increasing the relative motion improves hulling. Optimal impact parameters were obtained using a weighting method. The results of the study could improve the hulling performance of centrifugal rice hulling providing the basis improving the design. Highlights: Impact hulling relies on the relative motion between rice husk and brown rice. The effect of impact velocity and angle on hulling performance was investigated. The combined effect of impact and friction is key to the relative motion. The combined weighted scoring method was used to evaluate the hulling performance. Impact velocity of 35–40 m s −1, impact angle of 60°, are the optimum.